Transorbital Approach for Improved Access in the Management of Paranasal Sinus Mucoceles - Miller, Craig; Berens, Angelique; Patel, Sapna A.; Humphreys, Ian M.; Moe, Kris S. (Journal of Neurological Surgery Part B: Skull Base, 2019)
Introduction Paranasal sinus mucoceles result from obstruction of mucous glands resulting in a cystic fluid collection that expands and encroaches upon surrounding structures. Transnasal endoscopic marsupialization has largely replaced open resection. However, mucoceles located in the orbital region or the lateral frontal sinus continue to be difficult to approach via the transnasal approach alone and often require additional approaches, such as the frontal trephine. This study sought to investigate the feasibility of the transorbital technique as an adjunct to traditional transnasal approaches in the management of paranasal sinus mucoceles.Methods A retrospective case series of paranasal sinus mucoceles approached with a transorbital technique from a tertiary care center.Results From 2008 to 2016, 17 patients were treated with a transorbital approach for 20 mucoceles. Of note, 24% of the patients in our series had undergone previous surgical management of the mucocele (nontransorbital approach), representing revision cases. Most mucoceles involved the frontal sinus (82%). The total complication rate was 6%. We observed no new or worsened diplopia, ptosis, or permanent visual loss. Recurrence rate was 6%.Conclusions The endoscopic transorbital approach is a feasible complement to transnasal approaches for treatment of mucoceles located in technically challenging locations. We have demonstrated that transorbital approaches can be performed with no resultant orbital damage, visual change, ptosis, or permanent diplopia. While most patients can be treated with a standard transnasal approach, the transorbital approach can be used as part of a multiportal strategy for those with difficult to access mucoceles. Future prospective studies are needed to further characterize patient selection and outcomes.
Keywords: mucocele; anterior skull base; orbital/ocular; computer assisted surgery; endoscopic sinus surgery